Carica papaya L. Leaves: Deciphering Its Antioxidant Bioactives, Biological Activities, Innovative Products, and Safety Aspects. (9th June 2022) - Sharma, Anshu; Sharma, Ruchi; Sharma, Munisha; Kumar, Manoj; Barbhai, Mrunal Deepak; Lorenzo, José M.; Sharma, Somesh; Samota, Mahesh Kumar; Atanassova, Maria; Caruso, Gianluca; Naushad, Mo.; Radha; et al.
Abstract : The prevalence of viral infections, cancer, and diabetes is increasing at an alarming rate around the world, and these diseases are now considered to be the most serious risks to human well-being in the modern period. There is a widespread practice in Asian countries of using papaya leaves ( C. papaya L.) as herbal medicine, either alone or in combination with prescribed medications, to treat a variety of ailments. The importance of conducting the necessary descriptive studies in order to determine the safety of papaya leaf consumption is also emphasized in the context of their application in the healthcare sector. Electronic databases such as Google Scholar, Scopus, and PubMed were used to gather information on papaya leaves, their therapeutic potential, and clinical evidence-based studies. The literature was gathered from publications on papaya leaves, their therapeutic potential, and clinical evidence-based studies. The antidengue, anticancer, antidiabetic, neuroprotective, and anti-inflammatory effects of papaya leaves discussed in this article are supported by evidence from preclinical, in vivo, in vitro, and clinical trial studies, as well as from other sources. Leaves have been investigated for their mechanism of action as well as their potential to be used in the development of novel herbal products for the health business. According to the reports gathered, only a small number of research demonstrated that leaf extract at high concentrations was hazardous to certain organs. The collective literature reviewed in this review provides insights into the use of papaya leaves as a cure for epidemic diseases, highlighting the phytochemical composition and pharmacological attributes of papaya leaves, as well as the results of various preclinical and clinical studies that have been conducted so far on the subject. The review clearly demonstrates the successful medical evidence for the use of papaya leaf extracts in the healthcare system as a supplemental herbal medication in a variety of clinical settings.